HUBUNGAN ANTARA PENGETAHUAN ODAPUS DAN KEPATUHAN MINUM OBAT PADA ODAPUS MENGGUNAKAN METODE MMAS DAN LKQ DI MAGELANG - Harpeni Siswatibudi; Yuliana Sunariyati (Jurnal Permata Indonesia, 2022)
Background: Systemic Lupus Erythematosis (SLE) is a chronic autoimmune disease with various and complex manifestation and should be tailored individually. There’s many predisposing factors in treating SLE, and patients adherence is one of it. But in fact: there’s much of predisposing factors of adherence too. This study is one of the first step of comprehensive treatment intervention in medical way for patients with SLE, especially in Magelang region.Objective: General purpose of this research is to study the relationship of knowledge and treatment adherence in SLE patients using MMAS and LKQ methods in Magelang. The special purpose of this research are to study distribution frequency, knowledge and adherence levelof patients with SLE in Magelang.Method: This research is an correlation analitic research with cross sectional approach. The research data is obtained from 40 SLE patients in Magelang with total sampling technique. The data used in this research obtained from questionnaire. Test result obtained were analyzed using Kendall Tau Test.Result: The frequency distribution of adherence in SLE patients majorly low (28 respondents; 70.00%), meanwhile on the contrary: the knowledge frequency in most of SLE patients is average (24 respondent; 60.00%). Conclution: The result showed that the variables have no significant correlation between knowledge and SLE patients adherence (p-value 0,134 > α 0,05). Most of patients with SLE in Magelang are women (97.50%) in childbearing age (18-31 years old) (65.00%). Majority of subjects are housewives (32.50%) and high school graduate (52.50%). Most of them has been diagnosed within 3-5 years (40.00%), return to clinics in one month (90%), and consume more than 3 medications a day (52.50%). Most of patients consume combination of corticosteroid dan DMARDs or immunosuppressive agent (50.00%). Keywords: Lupus, Systemic Lupus Erythematosus, SLE, SLE patients, knowledge, adherence